Selective CO2 and H-2 adsorption in a chiral magnesium-based metal organic framework (Mg-MOF) with open metal sites - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Journal of Materials Chemistry, 2010)
A rare porous magnesium-based metal-organic framework, Mg-MOF-1 [Mg(3,5-PDC)(H2O)], was synthesized solvothermally in DMF. Structural determination by X-ray single-crystal diffraction technique reveals that this chiral MOF (space group P6(1)22) is constructed by helical assembly of Mg2+ ions with achiral 3,5-pyridine dicarboxylates and coordinating water molecules, to form a three-dimensional framework with parallel hexagonal channels. The structural detail of its 0D analogue Mg-MOF-2 [Mg(2,4-PDC)(H2O)(3)] has been discussed to show how subtle variation in the ligand architecture changes the resulting structure from 0D to 3D. Mg-MOF-1 remains robust and porous upon evacuation of the coordinating water molecules. This is the first report of a chiral hexagonal Mg-MOF synthesized from an achiral organic building unit. Open Mg metal sites show selective hydrogen (H-2) adsorption (ca. 0.8 wt% at 77 K) and carbon dioxide (CO2) uptake (ca. 0.7 mmol g(-1) at 298 K) over nitrogen at 1 atm. Ab initio quantum chemical calculation of adsorption energies and possible adsorption sites of hydrogen molecules are also reported.

Structural diversity in a series of metal-organic frameworks (MOFs) composed of divalent transition metals, 4,4 `-bipyridine and a flexible carboxylic acid - Pachfule, Pradip; Panda, Tamas; Dey, Chandan; Banerjee, Rahul (Crystengcomm, 2010)
A series of flexible metal-organic frameworks (MOFs) have been successfully synthesized under hydrothermal condition using 1,3-adamantanediacetic acid (C(14)H(20)O(4), H(2)ADA) as a flexible dicarboxylate building block, 4,4'-bipyridine and transition metal ions [Cd(II), Zn(II), and Mn(II)] as metal centers in DMF and aqueous media. These MOFs formulated as [Cd(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Cd-ADA-1), [Mn(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Mn-ADA-1), Zn(ADA)(4,4'-bipy)(0.5) (Zn-ADA-1), and [Mn(HADA)(2)(4,4'-bipy)(H(2)O)(2)] (Mn-ADA-2) (ADA = 1,3-adamantanediacetate, 4,4'-bipy = 4,4'-bipyridine and DMF = N,N'-dimethyl formamide) display interesting 1D, 2D and 3D structural features depending on the solvent of synthesis. All these MOFs were structurally determined by single-crystal X-ray diffraction. The coordination modes of this ligand are discussed and in addition, thermal stability and hydrogen (H(2)) and carbon-dioxide (CO(2)) adsorption properties of Cd-ADA-1, Mn-ADA-1 and Zn-ADA-1 are also presented. Hydrogen sorption at 77 K and up to 1 atm is found to be 0.42, 0.72 and 1.36 wt% without saturation for Zn-ADA-1, Mn-ADA-1 and Cd-ADA-1 samples.

Structural diversity in partially fluorinated metal organic frameworks (F-MOFs) composed of divalent transition metals, 1,10-phenanthroline, and fluorinated carboxylic acid - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Vanka, Kumar; Banerjee, Rahul (Crystal Growth & Design, 2010)
Seven new partially fluorinated metal-organic frameworks (F-MOFs) have been synthesized under different solvothermal conditions (H(2)O or N,N-dimethylformamide (DMF)) from transition metal cations [Zn(II), Co(II), and Mn(II)], 1,10-phenanthroline (phen), and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) to determine the influence of reaction conditions on the formation of metal-organic frameworks. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. Of the seven materials, two contain three-dimensional connectivity: Co(3)(hfbba)(6)(phen)(2) (F-MOF-6) and Mn(3)(hfbba)(6)(Phen)(2) (F-MOF-10). Three materials are one-dimensional structures: Zn(hfbba)(0.5)(phen)(HCO(2)) (F-MOF-8), Mn(Hhfbba)(2)(Phen) (F-MOF-11), and [Mn(hfbba)(2)(dm-phen)]center dot(H(2)O) (F-MOF-11A). Lastly, Co(hfbba)(phell)(2)center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-7) and Zn(hfbba)(phen)(2)center dot 2(H(2)hfbba) (H(2)O)-(HCO(2)) (F-MOF-9) are discrete zero-dimensional molecular complexes. F-MOF-6 and -10, which feature it three-dimensional (3D) framework with pcu topolgy are formed in DMF like F-MOF-8 and at 85 degrees C. The remaining F-MOFs are formed by a solvothermal reaction at 120 degrees C in water. F-MOF-7 and -9 are isostructural discrete zero-dimensional molecular complexes (a similar to 19.5; b similar to 13.7; c similar to 26.2/29.6 angstrom; beta similar to 99.9/120.04; V similar to 6840 angstrom(3)). All these F-MOFs were structurally determined by single-crystal X-ray diffraction. Solid-state properties such its UV-vis and the thermal stability of F-MOF-6 to -11A have also been studied. Insight into the factors influencing the preferred crystallization of a specific complex over others has been obtained from full quantum chemical (QM) calculations using density functional theory (DFT).

Structural, magnetic, and gas adsorption study of a two-dimensional tetrazole-pyrimidine based metal-organic framework - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2010)
A new two-dimensional (2D) metal-organic framework, Cu-TP-1, has been synthesized under solvothermal conditions (DMF) from the transition metal cation Cu(II) and 2-tetrazole pyrimidine (C5H5N6, H-TP). The structure has been determined by single crystal X-ray crystallography which shows a (6,3) honeycomb 2D net with perpendicular one-dimensional channels. Permanent porosity of Cu-TP-1 has been determined by the nitrogen adsorption isotherm. Cu-TP-1 show interesting H-2 and CO2 uptake. CO2 uptake of Cu-TP-1 (at 298 K, 1 atm pressure) is seen to be comparable to the recently reported ZIF-95 which outperforms ZIF-100 and BPL carbon. The magnetic properties show an antiferromagnetically coupled Cu ... Cu interaction down to 8 K with a Weiss temperature around 108 K.

Synthesis and structural comparisons of five new fluorinated metal organic frameworks (F-MOFs) - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Banerjee, Rahul (Crystengcomm, 2010)
A series of fluorinated metal-organic frameworks (F-MOFs) have been successfully synthesized under hydrothermal condition using 4,40-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) as a flexible dicarboxylate building block, Cu(+2) and various heterocyclic co-ligands. These F-MOFs formulated as [Cu(hfbba)(phen)(2)]center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-1), [Cu(hfbba)(2)(2,2'-bipy) 2(H(2)O)] (F-MOF-2), [Cu(hfbba)(4,4'-dime-2,2'-bipy)(HCO(2))]center dot(hfbba)(H(2)O) (F-MOF-3), [Cu(2)(hfbba)(2)(3-mepy)(2)]center dot(DMF) 2(3-mepy) (F-MOF-4), and [Cu(hfbba)(2)(phen)(2)]center dot 0.5(DMF) (F-MOF5) (hfbba = 4,4'-(Hexafluoroisopropylidene) bis(benzoate), phen 1,1'-phenanthroline; 2,2'-bipy 2,2'-bipyridine; 4,4'dime-2,2'-bipy 4,4'-dimethyl 2,2'-bipyridine; 3-mepy 3-methyl-pyridine and DMF dimethyl formamide) display interesting H-bonded, 1D and 2D structural features. All these F-MOFs were structurally determined by single-crystal X-ray diffraction. F-MOF-1 and 5 form a distorted octahedral Cu(+2) secondary building unit (SBU). F-MOF-5 forms a one-dimensional architecture constructed from Cu(2+) ions bridged by phen anions and two types of 4 hfbba ligands while in F-MOF-1, two among the three acid co-ligands are not coordinated with Cu(2+) ions. F-MOF-2 displays dinuclear SBUs within the three-dimensional frameworks whereas F-MOF-3 displays mononuclear SBUs and forms a one-dimensional chain. F-MOF-4 display a interesting 2D framework with conventional Cu(2)(CO(2))(4) paddle wheel SBU. In the crystal structures four hfbba ligands, each coordinated to a dicopper paddlewheel unit via one of their carboxylate groups. Solid-state properties such as UV-vis and thermal stability of F-MOF-1-5 have also been studied.

Solvothermal synthesis, structure, and properties of metal organic framework isomers derived from a partially fluorinated link - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Solvothermal reactions of Cu(NO3)(2) center dot 3H(2)O with 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba) and terminal monodentate ligand 3-methyl pyridine (3-picoline/3-mepy) in the presence of N, N-dimethyl formamide (DMF) and N,N-diethyl formamide (DEF) solvents gave rise to two structurally different two-dimensional (2D) fluorinated metal organic frameworks (F-MOFs). The effect of the choice of solvent has been clearly reflected in the structures obtained. The F-MOFs reported in this paper are formulated as [Cu-2(hfbba)(2)(3-mepy)(2)] center dot (DMF)(2)(3-mepy) (F-MOF-4), [Cu-2(hfbba)(2)(3-mepy)(2)] (Cu-F-MOF-4B), and [Zn-2(hfbba)(2)(3-mepy)(2)] center dot (3-mepy) (Zn-F-MOF-4B) which displays interesting 2D structures with and without interdigitation depending on the solvent used. The structures of these F-MOFs have been determined by X-ray crystallography and further identified by IR spectroscopy, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). The effect of interdigitation has been reflected in the gas adsorption and magnetic properties of these F-MOFs. These F-MOFs also show comparable H-2 and CO2 uptake depending on their structural variation. Temperature-dependent magnetic susceptibility measurements over a wide range of temperatures exhibit dominantly short-range antiferromagnetic behavior, with weak ferromagnetic behavior showing up at very low temperatures, which is evident from opening of the hysteresis loop with a finite value of coercivity in both F-MOF-4 and Cu-F-MOF-4B. We observed a smaller value of mu(eff) per Cu atom and coercivity in Cu-F-MOF-4B than the F-MOF-4 due to relatively larger distances between the neighboring dicopper paddlewheel secondary building unit.

Structural and gas adsorption study of a two-dimensional copper-tetrazole based metal-organic framework - Pachfule, Pradip; Banerjee, Rahul (Current Science, 2011)
A new two-dimensional (2D) metal organic framework, Cu-1(4-TBA)(1)(DMBP)(1).DMF (Cu-TBA-3), has been synthesized under solvothermal condition from transition metal cation Cu(II), predesigned ligand 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and coligand 4,4'-dimethy1-2,2'-bipyridine (DMBP). The structure has been determined by single crystal X-ray crystallography which shows layered 2D structure with square shaped one-dimensional channels. Cu-TBA-3 shows 0.69 wt% H-2 (at 77 K, 1 atm) and 1.65 mmol/g CO2 (at 298 K, 1 atm) uptake.
Keywords: CO2 capture; Hydrogen storage; metal-organic frameworks; microporous materials

Structural and selective gas adsorption studies of polyoxometalate and tris(ethylenediamine) cobalt(III) based ionic crystals - Dey, Chandan; Das, Raja; Pachfule, Pradip; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Seven new ionic solids built on polyoxometalate anions and [Co(en)(3)](3+) cations, namely, [Co(en)(3)Mo(8)O(26)(H(3)O)-(Cl)](DMF)(4)(H(2)O) (Co-Mo(8)-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DMF (Co-W(12)P-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)P-DEF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 5.5DMF (Co-Mo(12)P-DMF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 6DEF (Co-Mo(12)P-DEF), [alpha-SiW(12)O(40)]-[Co(en)(3)](3/2)[Cl](1/2)center dot 6DMF center dot 3H(2)O (Co-W(12)Si-DMF), and [alpha-SiW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)Si-DEF), have been synthesized from nonaqueous (DMF/DEF) media and characterized by single-crystal X-ray diffraction. We attempt to understand if [Co(en)(3)](3+) cations used in these reaction systems play a crucial role in controlling the assembly of these crystals. These ionic solids, after removal of the DMF or DEF molecules, are found to exhibit size selective H(2) adsorption properties over N(2). The amount of hydrogen adsorption was influenced by POM anion types and their orientations. CoMo(12)P-DEF has the highest (0.9 wt %) H(2) uptake, and CoW(12)P-DEF has the lowest (0.4 wt %) uptake among the series when the adsorbate pressure approached 1 atm.

Structural isomerism and effect of fluorination on gas adsorption in copper-tetrazolate based metal organic frameworks - Pachfule, Pradip; Chen, Yifei; Sahoo, Subash Chandra; Jiang, Jianwen; Banerjee, Rahul (Chemistry of Materials, 2011)
Synthesis, structure, and gas adsorption properties of three Metal Organic Frameworks (MOFs) synthesized from predesigned ligands 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and 2-fluoro-4-(1H-tetrazole-5-yl)benzoic acid (2F-4-TBA) along with Cu(II) as an metal precursor has been reported. Among these MOFs, Cu-9(4-TBA)(10)(C2H5OH)(2) (Cu-TBA-1) and Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) are structural isomers. Whereas, Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) and Cu-2(2-F-4-TBA)(2)(DMF)(2) (Cu-TBA-2F) have similar crystal structure. N-2 adsorption isotherms of the activated sample of Cu-TBA-1 and -2 exhibit types-I sorption behavior with a Langmuir and Brunauer-Emmett-Teller (BET) surface area of 686, 402 m(2)/g and 616, 356 m(2)/g, respectively. It is noteworthy that Cu-TBA-1 and -2 adsorbs 1.16 and, 1.54 wt % H-2, while Cu-TBA-2F adsorbs 0.67 wt % at 77 K and 1 atm. On the other hand, Cu-TBA-1 and -2 adsorb 3.08 and 2.54 mmol/g, while Cu-TBA-2F adsorbs 1.27 mmol/g of CO2 at 298 K and 1 bar pressure. H-2 adsorption sites in Cu-TBA-2 and -2F have been analyzed by molecular simulation.
Keywords: CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Structural, magnetic, and gas adsorption study of a series of partially fluorinated metal-organic frameworks (HF-MOFs) - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Inorganic Chemistry, 2011)
Four new partially fluorinated metal organic frameworks (HF-MOFs) have been synthesized under different solvothermal conditions (H2O or dimethylformamide (DMF)) from transition metal cations [Co2+ and Mn2+], 3-methyl pyridine (3-mepy) and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba), to determine the influence of reaction conditions on the formation of MOFs. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. HF-MOFs synthesized from H2O [Co-HFMOF-W, Co(liffiba)(3-mepy)(H2O) and Mn-HFMOF-W, Mn(hfbba)(3-mepy)(H2O)] contain three-dimensional connectivity whereas HF-MOFs synthesized from DmF Co-HFMOF-D, [Co-2(hfbba)(2)(3-mepy)(2)]center dot(DMF)(3) and Mn-HFMOE-D, [Mn-2(hfbba)(2)(3-mepy)]center dot(H2O) are two-dimensional in nature. Co-HFMOF-W and Mn-HFMOF-W are iso-structural polymeric materials. Thermal gravimetric analysis performed on as-synthesized HP-MOFs revealed that these compounds have high thermal stability (similar to 350 degrees C). The continuous decrease of the chi T product with decreasing T for Co-HFMOF-D and Co-HFMOF-W respectively indicates the presence of antiferromagnetic exchange interaction between two Co2+ (S = 3/2) metal centers within a duster.

Structure and gas sorption behavior of a new three dimensional porous magnesium formate - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Inorganic Chemistry, 2011)
A new three-dimensional magnesium formate polymorph, namely, gamma-[Mg-3(O2CH)(6)] has been synthesized via in situ formate anion generation method. gamma-Mg-formate crystallizes in space group Pbcn, and structural determination by X-ray single crystal diffraction reveals a three-dimensional network of Mg2+ linked by formate anions. All formate anions possess similar binding mode to the metal center with one oxygen of a particular formate anion binds to one metal center (mu(1) oxygen) and other oxygen binds to two metal centers (mu(2) oxygen). N-2 adsorption studies indicate that the framework displays permanent porosity. The specific surface area of gamma-Mg-formate (BET, 120 m(2) gm(-1)) is lower than the alpha- polymorph (BET, 150 m(2) gm(-1)). However, the initial hydrogen uptake of gamma-Mg-formate reached almost 1.0 wt % when the adsorbate pressure approached 760 Torr at 77 K. This is higher than the hydrogen uptake of alpha-Mg-formate (0.6 wt %). gamma-Mg-formate, shows a moderate affinity and capacity for CO2 (3.4 angstrom kinetic diameter) at 298 K. The CO2 uptake at 760 Torr is 2.01 mmol gm(-1)(47.0 cc gm(-1)). Although this CO2 uptake is somewhat modest, it compares well with the CO2 uptake of several Mg-MOFs and ZIFs reported in the literature.

Synthesis and structural characterization of a solvated dimorph of a hydrazonato-oxovanadium(v) complex with [OV(mu-O)VO] core - Mondal, Bipul; Banerjee, Rahul; Ghosh, Tapas (Journal of the Indian Chemical Society, 2011)
In this paper we report the synthesis and structural characterization of a different monoclinic variety of the title complex [V2O3(L)(2)], incorporating the doubly deprotonated benzoyl hydrazone of 5-chloro-2-hydroxyacetophenone (H2L) with P2(1)/c space group that showed some differences in bonding patterns in the solid state with respect to its another monoclinic variety with C2/c space group reported earlier.
Keywords: crystal structure; dimorphism; hydrazone complex; Oxovanadium(v) complex

Self-assembled one dimensional functionalized metal-organic nanotubes (MONTs) for proton conduction - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Two self-assembled isostructural functionalized metal-organic nanotubes have been synthesized using 5-triazole isophthalic acid (5-TIA) with In(III) and Cd(II). In-and Cd-5TIA possess one-dimensional (1D) nanotubular architecture and show proton conductivity along regular 1D channels, measured as 5.35 x 10(-5) and 3.61 x 10(-3) S cm(-1) respectively.

Solid phase morphological diversity of a rare vanadium cubane (V4O16) based metal organic framework - Dey, Chandan; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2012)
A Cu(II) connected V4O16-cubane based metal organic framework, Cu-2(phen)(2)(V4O8) (PO4)(4) [Cu2V4O16-2D] was synthesized under hydrothermal conditions. This is the first example of transition metal connected V4O16-cubane based MOF. X-ray single crystal data shows the alternate arrangement V4O16-cubane and Cu(phen)(O)(3) square pyramidal unit in two dimensions. These two-dimensional sheets are stacked on top of each other to form a three-dimensional architecture. Cu2V4O16-2D shows two types of solid state morphologies of the same phase, which was confirmed by scanning electron microscopy. It is noteworthy that this type of morphological difference of the solid phase in an extended metal organic hybrid material is rare and has not been perceived in the polyoxovanadate based MOFs literature. Cu2V4O16-2D was further characterized by powder X-ray diffraction (PXRD), thermal gravimetric analysis (TGA), IR-spectroscopy, scanning electron microscopy (SEM), and elemental analysis. We also studied the static magnetic and gas adsorption properties for Cu2V4O16-2D.

Solid-state thermolysis of anion induced metal-organic frameworks to ZnO microparticles with predefined morphologies: facile synthesis and solar cell studies - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
Simple one-step solid state thermolysis of two Zn-based homochiral metal organic frameworks (MOFs) leads to a dramatic difference in morphologies which depends on the anion (-Cl and -Br) and calcination environment (air and N-2). Rod-shaped (aspect ratio similar to 20), hexagonal column shaped (aspect ratio similar to 3), and elliptical aggregation of ZnO morphologies (aspect ratio similar to 3) are obtained and characterized. Although these two MOFs possess similar rod-shaped morphology, they produce dramatic change in resulting ZnO microparticle morphologies (from rod-shaped ZnO microparticles in the case of thermolysis of MOP 1 to hexagonal column shaped ZnO microparticles in the case of MOF 2 thermolysis) when calcined in N-2 at 800 degrees C. However, when we calcined both MOF 1 and 2 in air, we encountered similar elliptical aggregation of ZnO microparticles. These ZnO microparticles show permanent porosity, visible light emission centered at 605 or 510 nm. Moreover, they show 0.15% and 0.14% dye sensitized solar cell activity. To the best of our knowledge, this is the first report of dye sensitized solar cell activity of ZnO microparticles obtained from one-step thermolysis of porous homochiral MOFs.

Solution mediated phase transformation (RHO to SOD) in porous Co-imidazolate based zeolitic frameworks with high water stability - Biswal, Bishnu P.; Panda, Tamas; Banerjee, Rahul (Chemical Communications, 2012)
Here we report a highly porous, water stable Co based ZIF [CoNIm (RHO)] and its solution mediated phase transformation to a less porous and water unstable ZIF [CoNIm (SOD)]. CoNIm (RHO) has high Langmuir surface area [2087 m(2) g(-1)] as well as high water adsorption [200 cm(3) (STP) g(-1)] capacity.

Salt metathesis in three dimensional metal-organic frameworks (MOFs) with unprecedented hydrolytic regenerability - Kundu, Tanay; Sahoo, Subash Chandra; Saha, Subhadeep; Banerjee, Rahul (Chemical Communications, 2013)
{Eight Zn-based porous (1.2 nm) homochiral MOFs (ValZnX, AlaZnX

Stabilization of graphene quantum dots (GQDs) by encapsulation inside zeolitic imidazolate framework nanocrystals for photoluminescence tuning - Biswal, Bishnu P.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Banerjee, Rahul (Nanoscale, 2013)
Luminescent graphene quantum dots (GQDs) are encapsulated and stabilized in Zeolitic Imidazolate Framework (ZIF-8) nanocrystals. The GQDs are well confined due to the adsorption on the growing face of the ZIF-8 nanocrystals and have a profound effect on the shape of the nanocrystals from rhombic dodecahedron to spherical. Stabilizing GQDs inside the ZIF-8 nanocrystals results in tailoring of the photoluminescence emission (ca. 32 nm, bathochromic shift) of the GQD@ZIF-8 nanocrystal composite even after 3 months of aging under normal laboratory conditions. Also the water adsorption (at STP) capacity increased for the GQD@ ZIF-8 composite as compared to the pristine ZIF-8.

Structural design of coordination polymers - Du, Miao; Banerjee, Rahul; Shimizu, George K. H. (Crystengcomm, 2013)

Structural isomerism leading to variable proton conductivity in indium(III) isophthalic acid based frameworks - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2013)
Proton conductivity has been studied thoroughly in two isomeric In(III)-isophthalate based MOFs. In-IA-2D-1 is capable of showing proton conductivity (3.4 x 10(-3) S cm(-1)) under humidified conditions (98% RH), whereas In-IA-2D-2 can conduct protons (2.6 x 10(-5) S cm(-1)) under humidified as well as anhydrous conditions.

Synthesis, structure, and H-2/CO2 adsorption in a three-dimensional 4-connected triorganotin coordination polymer with a sqc topology - Chandrasekhar, Vadapalli; Mohapatra, Chandrajeet; Banerjee, Rahul; Mallick, Arijit (Inorganic Chemistry, 2013)
A 4-connected triorganotin 3D coordination polymer in a sqc topology has been shown to possess 1D microchannels along its crystallographic a axis. This main-group-element-containing framework structure shows selective gas adsorption, preferring CO2 and H-2 over N-2.

Structural diversity in serine derived homochiral metal organic frameworks - Kundu, Tanay; Banerjee, Rahul (Journal of Chemical Sciences, 2014)
Two new Zn(II) and Cd(II) based homochiral metal-organic frameworks (MOFs) [SerCdOAc and Zn(Ser)(2)] have been synthesized using pyridyl functionalized amino acid, viz., serine, as an organic linker. The SerCdOAc structure is three dimensional, while that of the Zn(Ser)(2) is two dimensional. The polar voids of the corresponding MOFs are filled with solvent molecules (water in the case of SerCdOAc and methanol in the case of Zn(Ser)(2)). In both cases, metal centres, i.e., Zn(II) and Cd(II), are hexacoordinated. However, with a change in the solvent for synthesis, ligand coordination mode and incorporation of additional coordinated anion resulted in a great change in the final MOF architecture. Herein, for the first time, we could achieve structural variety and synthesize MOFs composed of only metal ion and pyridyl functionalized amino acid linker.
Keywords: Amino acid; crystal engineering; hydrogen bonding; metal organic framework

Sulfonic acid loaded self-standing covalent organic membrane for proton conduction - Sasmal, Himadri Sekhar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COF; Membrane; proton conduction

Supramolecular gel to metal organic framework transformation - Chakraborty, Amit; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: gel; MOF; Supramolecular

Selective interfacial synthesis of metal-organic frameworks on a polybenzimidazole hollow fiber membrane for gas separation - Biswal, Bishnu P.; Bhaskar, Anand; Banerjee, Rahul; Kharul, Ulhas K. (Nanoscale, 2015)
Metal-organic frameworks (MOFs) have gained immense attention as new age materials due to their tuneable properties and diverse applicability. However, efforts on developing promising materials for membrane based gas separation, and control over the crystal growth positions on polymeric hollow fiber membranes still remain key challenges. In this investigation, a new, convenient and scalable room temperature interfacial method for growing MOFs (ZIF-8 and CuBTC) on either the outer or inner side of a polybenzimidazole based hollow fiber (PBI-BuI-HF) membrane surface has been achieved in a controlled manner. This was made possible by the appropriate selection of an immiscible solvent pair and the synthetic conditions. The growth of MOFs on the PBI-BuI-HF membrane by the interfacial method was continuous and showed an appreciable gas separation performance, conveying promise for their applicability.

Self-templated chemically stable hollow spherical covalent organic framework - Kandambeth, Sharath; Venkatesh, V.; Shinde, Digambar B.; Kumari, Sushma; Halder, Arjun; Verma, Sandeep; Banerjee, Rahul (Nature Communications, 2015)
Covalent organic frameworks are a family of crystalline porous materials with promising applications. Although active research on the design and synthesis of covalent organic frameworks has been ongoing for almost a decade, the mechanisms of formation of covalent organic frameworks crystallites remain poorly understood. Here we report the synthesis of a hollow spherical covalent organic framework with mesoporous walls in a single-step template-free method. A detailed time-dependent study of hollow sphere formation reveals that an inside-out Ostwald ripening process is responsible for the hollow sphere formation. The synthesized covalent organic framework hollow spheres are highly porous (surface area similar to 1,500m(2) g(-1)), crystalline and chemically stable, due to the presence of strong intramolecular hydrogen bonding. These mesoporous hollow sphere covalent organic frameworks are used for a trypsin immobilization study, which shows an uptake of 15.5 mu mol g(-1) of trypsin.

Single crystal-to-single crystal site-selective postsynthetic metal exchange in a Zn-MOF based on semi-rigid tricarboxylic acid and access to bimetallic MOFs - Bajpai, Alankriti; Chandrasekhar, Pujari; Govardhan, Savitha; Banerjee, Rahul; Moorthy, Jarugu Narasimha (Chemistry-A European Journal, 2015)
The metal ions in a neutral Zn-MOF constructed from tritopic triacid H3L with inherent concave features, rigid core, and peripheral flexibility are found to exist in two distinct SBUs, that is, 0D and 1D. This has allowed site-selective postsynthetic metal exchange (PSME) to be investigated and reactivities of the metal ions in two different environments in coordination polymers to be contrasted for the first time. Site-selective transmetalation of Zn ions in the discrete environment is shown to occur in a single crystal-to-single crystal (SCSC) fashion, with metal ions such as Fe3+, Ru3+, Cu2+, Co2+, etc., whereas those that are part of 1D SBU sustain structural integrity, leading to novel bimetallic MOFs, which are inaccessible by conventional approaches. To the best of our knowledge, site-selective postsynthetic exchange of an intraframework metal ion in a MOF that contains metal ions in discrete as well as polymeric SBUs is heretofore unprecedented.
Keywords: coordination polymers; metal-exchange; metal-organic frameworks; Metathesis; X-ray crystallography

Solid state organic amine detection in a photochromic porous metal organic framework - Mallick, Arijit; Garai, Bikash; Addicoat, Matthew A.; Petkov, Petko St.; Heine, Thomas; Banerjee, Rahul (Chemical Science, 2015)
A new Mg(II) based photochromic porous metal-organic framework (MOF) has been synthesized bearing naphthalenediimide (NDI) chromophoric unit. This MOF (Mg-NDI) shows instant and reversible solvatochromic behavior in presence of solvents with different polarity. Mg-NDI also exhibits fast and reversible photochromism via radical formation. Due to the presence of electron deficient NDI moiety, this MOF exhibits selective organic amine (electron rich) sensing in solid state. The organic amine detection has been confirmed by photoluminescence quenching experiment and visual color change.

Self-exfoliated metal-organic nanosheets through hydrolytic unfolding of metal-organic polyhedra - Garai, Bikash; Mallick, Arijit; Das, Anuja; Mukherjee, Rabibrata; Banerjee, Rahul (Chemistry-A European Journal, 2016)
Few-layers thick metal-organic nanosheets have been synthesized using water-assisted solid-state transformation through a combined top-down and bottom-up approach. The metal-organic polyhedra (MOPs) convert into metal-organic frameworks (MOFs) which subsequently selfexfoliate into few-layered metal-organic nanosheets. These MOP crystals experience a hydrophobicity gradient with the inner surface during contact with water because of the existence of hydrophobic spikes on their outer surface. When the amount of water available for interaction is higher, the resultant layers are not stacked to form bulk materials; instead few-layered nanosheets with high uniformity were obtained in high yield. The phenomenon has resulted high yield production of uniformly distributed layered metal-organic nanosheets from three different MOPs, showing its general adaptability.

State-of-the-art catechol porphyrin COF catalyst for chemical fixation of carbon dioxide via cyclic carbonates and oxazolidinones - Saptal, Vitthal; Shinde, Digambar Balaji; Banerjee, Rahul; Bhanage, Bhalchandra M. (Catalysis Science & Technology, 2016)
A highly porous, crystalline catechol porphyrin COF was synthesized and applied as an organocatalyst for the chemical fixation of carbon dioxide to synthesize value-added chemicals such as cyclic carbonates and oxazolidinones under solvent-free and transition-metal-free conditions. The high surface area and the functionalities of the COF catalyst act synergistically to activate the starting material. The 2,3-DhaTph shows excellent activity towards cyclic carbonates at the atmospheric pressure of carbon dioxide. Additionally, this catalytic system is recyclable in nature and provides a higher turnover number than previously reported organocatalysts.

Supramolecular metallogel that imparts self-healing properties to other gel networks - Feldner, Tobias; Haering, Marleen; Saha, Subhadeep; Esquena, Jordi; Banerjee, Rahul; Diaz, David Diaz (Chemistry of Materials, 2016)
A unique proton conductive and moldable supramolecular metallogel (CuA-Ox-gel) made upon mixing at room temperature well-defined stock solutions of Cu(OAc)(2). H2O and oxalic acid dehydrate was found to have self-healing properties. Remarkably, the system also displayed an unprecedented ability to impart self-healing properties to other gel networks lacking this capacity. A self-healed CuA-Ox metallogel was found to have essentially the same nanofibrillar morphology, thermal stability, rheological properties, and conductivity as the freshly prepared sample. The discovery also allowed the fabrication of self-healing conductive composites containing conductive carbonaceous materials. Overall, this work serves as a proof of concept for the transfer of self-healing properties between completely different gel networks.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.

Synthesis, characterization and electrochemical investigations of mixed-ligand copper(II)-organic supramolecular frameworks - Singh, Sandeep K.; Srivastava, Ashish Kumar; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Journal of Molecular Structure, 2017)
Two mixed-ligand copper(II)-organic coordination compounds with 5,5'-dimethyl-2,2'-bipyridine (5,5'-Me(2)bpy) as a primary ligand while aliphatic malonate (Hmal) and aromatic 2-hydroxynicotinate (2-OHNA) as secondary ligands, were synthesized. These complexes are formulated as: [Cu(Hmal)(5,5'-Me(2)bPY)(H2O)](ClO4) 1 and [Cu-2(2-OHNA)(2)(5,5'-Me(2)bpy)(2)(NO3)KNO3) 2. These two complexes were structurally characterized by single crystal X-ray diffraction analysis. Characterization was further supported by powder X-ray diffraction analysis, elemental analyses, FT-IR, FAB-MASS and TGA, DSC studies. Cyclic voltammetric and UV-visible spectral studies of these two complexes have also been done. The electrochemical studies of complex 1 in DMSO and DMF have shown that this complex undergoes quasi reversible diffusion-controlled one-electron transfer reaction without any chemical complication while complex 2 in DMSO undergoes quasi-reversible diffusion-controlled one electron transfer reaction, following EC mechanism. The electrochemical behaviour of complex 2 in DMF is complicated probably due to presence of more than one species in solution phase. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 2 '-bipyridine; 3; 5; 5 '-dimethyl-2; 5-Tricarboxylic acid; Benzene-1; classification; Co-ordination-Compounds; Crystal-structures; cyclic voltammetry; magnetic properties; metal organic framework; Mixed-ligand complex; pi-pi stacking interaction; Polymers; Secondery Building Unit; Structural data; Supramolecular framework; Ternare Komplexe; X-ray diffraction

Superprotonic conductivity in flexible porous covalent organic framework membranes - Banerjee, Rahul; Sasmal, Himadri Sekhar; Harshitha, B. A.; Bhange, Siddheshwar; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar (Angewandte Chemie, 2018)
Poor mechanical stability of the polymer electrolyte membranes (PEMs) remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded covalent organic framework membranes (COFMs) showing the highest proton conductivity amongst all crystalline porous organic polymeric materials reported till date, as high as 7.8 x 10‐2 S cm‐1, have been further tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm‐2 power density, which is the highest among COFs and MOFs, highlights the possibilityof using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.

Supramolecular reassembly of self-exfoliated ionic covalent organic nanosheets for label-free detection of double-stranded DNA - Mal, Arindam; Mishra, Rakesh K.; Praveen, Vakayil K.; Khayum, M. Abdul; Banerjee, Rahul; Ajayaghosh, Ayyappanpillai (Angewandte Chemie-International Edition, 2018)
Ionic covalent organic nanosheets (iCONs), a member of the two-dimensional (2D) nanomaterials family, offer a unique functional platform for a wide range of applications. Herein, we explore the potential of an ethidium bromide (EB)-based covalent organic framework (EB-TFP) that self-exfoliates in water resulting in 2D ionic covalent organic nanosheets (EB-TFP-iCONs) for the selective detection of double-stranded DNA (dsDNA). In an aqueous medium, the self-exfoliated EB-TFP-iCONs reassemble in the presence of dsDNA resulting in hybrid EB-TFP-iCONs-DNA crystalline nanosheets with enhanced fluorescence at 600 nm. Detailed steady-state and time-resolved emission studies revealed that the reassembly phenomenon was highly selective for dsDNA when compared to single-stranded DNA (ssDNA), which allowed us to use the EB-TFP-iCONs as a 2D fluorescent platform for the label-free detection of complementary DNA strands.
Keywords: Covalent organic framework; DNA; ionic assembly; ionic covalent organic nanosheets; label-free detection

Syntheses and single crystal X-ray diffraction analysis of five isostructural 2D MOCCs - Singh, Sandeep K.; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Polyhedron, 2018)
Five two-dimensional metal-organic coordination compounds (MOCCs) have been solvothermally synthesized by the combination of 2-aminonicotinic acid (ANA) and transition metal ions, viz. Co(II), Ni (II), Cu(Il), Zn(II) and Cd(II), in water-ethanol mixed solvent. They are formulated as [CoC6H5N2O2)(2)], (Co-ANA); [Ni(C6H5N2O2)(2)], (Ni-ANA) [Cu(C6H5N2O2)(2)], (Cu-ANA), [Zn(C6H5N2O2)(2)], (Zn-ANA) and [Cd(C6H5N2O2)(2)], (Cd-ANA). Single crystal X-ray diffraction studies for the complexes Co-ANA, Ni-ANA and Cd-ANA have also been carried out. These three complexes crystallize in the tetragonal crystal system with the space group P4(1)2(1)2. The metal ions in all these complexes have an octahedral coordination environment. The six coordinations are satisfied by two pyridine N-atoms from two different ANA ligands and four oxygen atoms from two chelating carboxylate groups of another two ANA ligands. The topological motif of the coordination network is defined as 2-periodic net or square lattice (sql). These complexes were further characterized by elemental, FT-IR spectral, thermal and powder X-ray diffraction analyses. (C) 2018 Elsevier Ltd. All rights reserved.